London-van der Waals Force Field of a Chemically Patterned Surface to Enable Selective Adhesion - Jaiswal R.P.; Beaudoin S.P. (My University, 2025)
The London-van der Waals (L-vdW) force between a particle and a surface strongly depends on the topography and the chemical properties of the interacting surfaces. Although a great deal of work has been done to understand the effect of topographical heterogeneity on the L-vdW adhesion, the role of chemical heterogeneity has been discussed only rarely. This study makes an attempt to quantify the magnitude and range of the L-vdW force acting on a spherical particle in the vicinity of a chemically patterned surface. Specifically, an ideal system of a smooth spherical particle approaching a surface composed of parallel stripes of chemically distinct materials with different Hamaker constants is considered. The L-vdW forces for such systems are determined by solving the London dispersion potential for the entire volumes of the adhering bodies from first principles, using Hamaker's microscopic approach. The computational results elucidate that a chemical interface can apply a tangential L-vdW force, in addition to the normal L-vdW force, on nearby particles. This can cause lateral motion of particles neighboring a chemically inhomogeneous surface. The magnitude of the tangential L-vdW force is found to be maximum when the particle is centered at the interface and shows a gradual drop as it moves away from this location. The magnitude and range of the tangential L-vdW force can be large for large colloidal particles in close contact with a chemically patterned surface whose materials have distinct Hamaker constants. This study suggests that the tangential L-vdW force field generated by a chemical interface can be utilized as a tool to manipulate the path of an approaching particle to facilitate selective adhesion. © 2018 American Chemical Society.